CORPORATE TAX AVOIDANCE PRACTICES: AN EMPIRICAL EVIDENCE FROM NIGERIAN FIRMS - ADEGBITE, Tajudeen Adejare; BOJUWON, Mustapha (Studia Universitatis Babeș-Bolyai Oeconomica, 2019)
This study examined the existence of corporate tax avoidance practices among the public listed firms in Nigeria. Secondary data were obtained from annual published reports from selected Nigerian firms listed in Nigeria stock exchange from 2006 to 2017. Panel Data analysis technique was used to analyse the effect of independent variables (Thin capitalization, Leverage, Firms Size, Transfer Pricing, and Intangible Assets) on dependent variable (Corporate Tax Avoidance). The result showed that thin capitalisation, firm size, profitability, leverages, intangible assets, and transfer pricing are significantly related with corporate tax avoidance. Thin capitalisation, profitability and transfer pricing are the primary driver of corporate tax avoidance. It is concluded that there are several corporate tax avoidance practices employed by Nigerian firms to aggressively reduce their corporate tax liabilities in Nigeria. JEL Classification: H26, G31, H29, L25, L11, E22